Phase II trial of nivolumab monotherapy and biomarker screening in patients with chemo‐refractory germ cell tumors. (23rd April 2022) - Kawahara, Takashi; Kawai, Koji; Kojima, Takahiro; Nagumo, Yoshiyuki; Sakka, Shotarou; Kandori, Shuya; Negoro, Hiromitsu; Mathis, Bryan J; Maruo, Kazushi; Miura, Koji; Sakamoto, Noriaki; Shinohara, Nobuo; et al.
Abstract : Objectives: Germ cell tumors are highly susceptible to chemotherapy; however, there is a lack of established treatments for consistently relapsing germ cell tumor. Therefore, in this phase II study, we evaluated the efficacy and safety of nivolumab for relapsed germ cell tumor. Methods: Seventeen adult patients (median age 34 years) with refractory primary germ cell tumor after second‐line or higher chemotherapy were enrolled. Nivolumab was administered over 30 min at 240 mg/body every 2 weeks until disease progression or intolerable adverse event occurrence. The primary endpoint was the overall response rate. Result: We performed a biomarker analysis of programmed death ligand‐1 expression and genomic sequencing. Tumor histology revealed nonseminoma and seminoma in 14 and three patients, respectively. Patients were pretreated with a median of three chemotherapy lines, and three patients received high‐dose chemotherapy. The median number of nivolumab doses was 3 (range 2–46). One patient showed a partial response and three showed stable disease. Responses were durable in one patient with a partial response and one patient with stable disease (median 90 and 68 weeks, respectively). Nivolumab was well‐tolerated, with only two Grade 3 adverse events observed. Programmed death ligand‐1 expression was not associated with objective responses. Genomic sequencing revealed a high tumor mutation burden in a patient with a durable partial response. While a small subset of chemorefractory germ cell tumors may respond to nivolumab, programmed death ligand‐1 is unreliable to measure response. Conclusions: Tumor mutation burden is a potential biomarker for future testing of germ cell tumor response.